2022
DOI: 10.1371/journal.pone.0266533
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis and microbiome profile of patients in a referral gastrointestinal diseases centre in the Sudan

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) causes Johne’s disease in animals with zoonotic potential; it has been linked to many chronic diseases in humans, especially gastrointestinal diseases (GID). MAP has been extensively studied in Europe and America, but little reports were published from Africa. Sudan is a unique country with close contact between humans and livestock. Despite such interaction, the one health concept is neglected in dealing with cases of humans with GID. In this study, patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…In the case of Planococcaceae , no population was observed in any MAP-infected animals in this study. In addition, the genera Alistipes (negative, 4.65 ± 1.52; positive, 2.94 ± 0.86; Mann-Whitney U test, P < 0.001) and Paraprevotella (negative, 0.13 ± 0.15; positive, 0.08 ± 0.11; Mann-Whitney U test, P < 0.001) were significantly decreased by MAP infection in this study, which is consistent with other studies ( 36 , 37 ), whereas the overrepresentation of Firmicutes (negative, 56.18 ± 7.09; positive, 62.83 ± 7.33; Mann-Whitney U test, P < 0.01), Enterococcus (negative, 0.03 ± 0.06; positive, 0.07 ± 0.05; Mann-Whitney U test, P < 0.001), and Streptococcus (negative, 0.03 ± 0.09; positive, 0.08 ± 0.12; Mann-Whitney U test, P < 0.05) in the MAP-infected group was observed, which was also reported for MAP-infected animals and humans ( 37 , 38 ). In the case of Actinobacteria , there is controversy regarding its population change due to MAP infection.…”
Section: Discussionsupporting
confidence: 76%
“…In the case of Planococcaceae , no population was observed in any MAP-infected animals in this study. In addition, the genera Alistipes (negative, 4.65 ± 1.52; positive, 2.94 ± 0.86; Mann-Whitney U test, P < 0.001) and Paraprevotella (negative, 0.13 ± 0.15; positive, 0.08 ± 0.11; Mann-Whitney U test, P < 0.001) were significantly decreased by MAP infection in this study, which is consistent with other studies ( 36 , 37 ), whereas the overrepresentation of Firmicutes (negative, 56.18 ± 7.09; positive, 62.83 ± 7.33; Mann-Whitney U test, P < 0.01), Enterococcus (negative, 0.03 ± 0.06; positive, 0.07 ± 0.05; Mann-Whitney U test, P < 0.001), and Streptococcus (negative, 0.03 ± 0.09; positive, 0.08 ± 0.12; Mann-Whitney U test, P < 0.05) in the MAP-infected group was observed, which was also reported for MAP-infected animals and humans ( 37 , 38 ). In the case of Actinobacteria , there is controversy regarding its population change due to MAP infection.…”
Section: Discussionsupporting
confidence: 76%
“…However, our experience with human faecal cultures for MAP made at the same time is in total contrast to these findings. We found that culture is more sensitive than DNA detection by real-time PCR for MAP in human faecal or tissue samples [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Countrywide investigations would reveal the prevalence of the disease in other states. Besides being a production-limiting disease, it is gaining more public health importance as the association between MAP and some human diseases is garnering more support [ 7 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…( Arumugam et al., 2011 ; Carrière et al., 2014 ), Actinobacteria (e.g., Mycobacterium avium subsp. paratuberculosis) ( McNees et al., 2015 ; Elmagzoub et al., 2022 ), and also viruses (e.g., norovirus, polyomavirus, anellovirus, herpesvirus, adenovirus, sapovirus, rotavirus) ( Haag et al., 2015 ; Lecuit and Eloit, 2017 ; Cao et al., 2022 ; Matsuzawa-Ishimoto et al., 2022 ; Dehghani et al., 2023 ; Ding et al., 2023 ) and fungi (e.g., Candida spp. ) ( Šašala et al., 2020 ; Di Martino et al., 2022 ).…”
Section: Crohn’s Diseasementioning
confidence: 99%